Immortality Through Love in Shakespearian Sonnets - Imsallim, Wraida Marai; Imsallim, Reem Marai (مجلة كلية الاداب, 2022)
This paper is a close analysis of immortality in Shakespearian sonnets. First, the researcher defines sonnets in general defining the two types of sonnets, then narrows it down to Shakespearian sonnets: a history of the sonnets, to whom where they addressed to and the themes they discuss. To Shakespeare immortality is achieved through three ways, through procreation, through verse and immortality through love. This paper addresses the latter, analyzing samples from sonnets 15, 22, 25, 26, 55, 108, 115, 116, 123 and 124 and providing them with deeper analysis. These sonnets are chosen because they deal with the theme of immortality through love in Shakespearian sonnets.